Defeitos intrínsecos e impurezas em nanofios de InN - Silva, Júlio César da (2014)
Group III nitride semiconductors have a huge potential for applications in photodetectors and efficient solar cells. With the recent discovery of the InN band gap of about 0.7 eV, this might be a semiconductor nitride important for the industry. More than that, nanostructures using InN can be built with different gaps of energy when combined with other elements or the creation of defects, which is desired for different technological applications. However, the doping in InN is a difficult task, especially in p-type systems. This study investigates intrinsic defects such as In and N vacancies, as well as extrinsic defects using Mg impurities. Mg is a good dopant in InN, because it can be a p-type or n-type depending upon how the defect is incorporated in the system, since the Mg doping has a direct influence on the Fermi level. Our results for Mg defects substitutional at In site and interstitial show energetically favorable structures. It was found that N vacancy, Mg interstitial and Mg substitutional at N site in bulk and InN nanowire are n-type semiconductor; while In vacancy and Mg substitutional at In site are p-type semiconductors. InN nanowires have a band gap larger than the bulk band gap, which occurs due to quantum confinement effects. For InN nanowires, the lowest formation energies are found for Mg substitutional at In site, and Mg interstitial, which are p-type and n-type, respectively. This results are very similar to that found for the InN bulk. The formation energy values are somewhat smaller in bulk than in InN nanowire. We also study charged defects, where we observed that In vacancy and Mg substitutional at In site tend to gain electrons since they have lower formation energies for 1- and 2- charged defects. On the other hand, the opposite occurs for N vacancy, Mg interstitial and Mg substitutional at N site tend to lose electrons, since they have lower formation energies for 1+ and 2+ charged defects.